Folklore as a Linguocultural Factor in Enriching the American and Canadian Variants of English. (Eurasian Journal of Philology Science and Education, 2015)
Oral national literature was formed in the course of evolution. Earlier the religious and mythological ideas of people were very rich, subsequently oral national literature and folklore developed, and as a result the language has enriched. The process of social stratification in society generated separate types, genres and art forms of the spoken word, expressing the goals and interests of different social groups and layers. The connection with the comparative creativity became the reason of the variety of texts of oral national literature. The stability of folklore texts is explained not only by human values, but also by slow changes in the way of life, outlook and aesthetic taste of people considered to be their main creator.
Keywords: folklore; linguistics; culture; English